Antagonstic Effect of Lactobacillus Fermentum Supernatant AgainstEnterococcus Faeciumand Enterococcus Faecalis In Vitro - Mahdi, Likaa H.; Husain, Sanaa N. (Journal of the Faculty of Medicine Baghdad, 2012)
Background:Lactobacillus fermentum selected as an alternative treatment to prevent or treat urogenital infection based on their probiotics properties and production of bacteriocins.Objective: The present work was done to study the inhibition activity of L. fermentum cell free supernatant against urogenital pathogens Enterococcus faecium and Enterococcus faecalisinvitro.Materials and methods: L.fermentum isolates have been collected from vaginal swabs . A supernatant of these isolates has been prepared and its antibacterial activity against 3 isolates of E.faecium and 3 isolates of E.faecalis has been studied.Results: Different concentrations have been prepared and the most effective one was 1000μg/ml and the most affected isolate of E.faecalis was no. 3 which its MIC was 64μg/ml and MBC was 128 μg/ml, while the most affected isolate of E. faecium was no. 1 which its MIC was 128 μg/ml and MBC was 256 μg/ml .Conclusion:L. fermentumCFS showed significant activity against both Enterococcus isolates and showed closely related results.